2005
DOI: 10.2112/03-105a.1
|View full text |Cite
|
Sign up to set email alerts
|

A Model of the 3D Circulation, Salinity Distribution, and Transport Pattern in the Pearl River Estuary, China

Abstract: JONSSON, L.; CHEN, C, and SHI, P. 2005, A model of the 3D circulation, salinity distribution, and transport pattern in the pearl river estuary, China, Journal of Coastal Research, 21(5), 896-908, West Palm Beach (Florida), ISSN 0749-0208,The three-dimensional circulation, salinity distrihution, and overall transport pattern were simulated in the Pearl River Estuary, China, using a modified version of the Princeton Ocean Model (POM), The circulation in the estuary is mainly driven by tide, wind, and river runof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 15 publications
(7 reference statements)
1
14
0
Order By: Relevance
“…The overall transport trend of diluted water from the estuary out into the SCS was along the western boundary of the estuary in both the summer and winter (Larson et al, 2005). Several studies have reported lower primary production due to high turbidity within the river plume (Hu et al, 2006;Yin et al, 2004b).…”
Section: Pp Biomass and Spatial Distribution In Three Contrasting Permentioning
confidence: 99%
“…The overall transport trend of diluted water from the estuary out into the SCS was along the western boundary of the estuary in both the summer and winter (Larson et al, 2005). Several studies have reported lower primary production due to high turbidity within the river plume (Hu et al, 2006;Yin et al, 2004b).…”
Section: Pp Biomass and Spatial Distribution In Three Contrasting Permentioning
confidence: 99%
“…O1, Q1, P1, K1, N2, M2, MU2, NU2, S2, K2, M4 and MS4) and a compensation to include the coastal currents associated with the dry or wet season conditions by tilting the offshore model boundaries. The latter approach, introduced by Uittenbogaard and Hulsen (1999), helped to provide efficient estimates of the coastal currents, see also Larson et al (2005), while avoiding the application of larger-scale models, as for instance used by Wong et al (2003).…”
Section: Modelling Set Upmentioning
confidence: 99%
“…The Lingding Bay, called the "Zhujiang Estuary (ZE)" in this paper, receives about 60% of the total Zhujiang River discharge (Zhao, 1990) through four major inlets of Humen, Jiaomen, Hongqili and Hengmen (Figs 1a and b). The bell-shaped semi-closed ZE is the largest estuary of the Zhujiang River with an area of 2 500 km 2 (Larson et al, 2005). The northern end width of the ZE is only 5 km but 60 km for the southern end.…”
Section: Introductionmentioning
confidence: 99%
“…During the dry season, from October to April, northeast monsoon dominates the ZE and the mean rainfall is only about 3-4 cm/month (Ding, 1994;Harrison et al, 2008). In the wet season, from May to August, southwest monsoon brings the warm and humid air and leads to large rainfall amount to 30-40 cm/month (Larson et al, 2005). Thus, the mean fresh water discharged into the ZE is 1 500 m 3 /s in the dry season but 20 000 m 3 /s in the wet season (Zhao, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation